Thermal stability of Sn anode material with non-aqueous electrolytes in sodium-ion batteries - Lee, Yongho; Lim, Hyojun; Kim, Sang-Ok; Kim, Hyung-Seok; Kim, Ki Jae; Lee, Kwan-Young; Choi, Wonchang (ROYAL SOC CHEMISTRY, 2018)
The thermal behavior of fully lithiated and sodiated Sn electrodes cycled in a MePF6 (Me = Li or Na)-based electrolyte was studied using differential scanning calorimetry (DSC). The sodiated Sn electrode cycled in the NaPF6-based electrolyte showed a thermal reaction with much greater heat generation (1719.4 J g(-1)) during the first exothermic reaction corresponding to the thermal decomposition reaction of the solid electrolyte interface (SEI) layer, compared to that of the lithiated Sn electrode (647.7 J g(-1)) in the LiPF6-based electrolyte because of the formation of a thicker surface film on the Sn electrode. The NaPF6-based electrolyte yielded a slightly less conductive and/or a thicker SEI layer than the NaClO4-based electrolyte, resulting in the intense thermal decomposition of the SEI layer. The DSC results for the fully sodiated Sn electrode cycled in FEC-containing electrolytes clearly demonstrate that an exothermic reaction corresponding to the SEI decomposition mostly disappears because of the formation of a thermally stable and thin SEI layer on active materials via the electrochemical decomposition of FEC. X-ray photoelectron spectroscopy reveals the formation of SEI with a relatively high proportion of NaF, which is known to be a thermally stable inorganic solid at high temperatures.